El plazo de la licencia por paternidad y la igualdad como derecho fundamental - Azabache Torres, Pedro Jorge (2017)
The Labor Law has allowed analyzing and understanding diverse types of suspensions of the work contract, finding between them a paternity leave, national legislation grants paid leave of four days to working parents - Law N° 29409; however, the law is insufficient, as they do not allow an adequate reconciliation of work and family life. It is for this reason that it has been reviewed in foreign legislations that paternity leave periods are longer, and also contain factual assumptions that allow a longer license. In Latin America, we are the country that grants the least number of days for the paternity leave; however, Ecuador grants ten days of leave and with different factual assumptions that increase the duration of the paternity leave. To analyze the period of paternity leave and the connection that it has with the equality right, we studied paternity from the point of view of Psychology and Sociology, but mainly, compared with the maternity leave, with the purpose of verifying the Existence of inequality. Finally, we propose a legislative initiative, by means of which we propose the modification of article 2 of Law No. 29409, suggesting the increase the period of the paternity leave to fifteen consecutive days, and the legal regulation of special cases that would increase the period of the paternity leave, such as multiple birth, cesarean birth, newborn disease, anyway